Dual interface engineering of NiO/NiCo2O4/CoO heterojunction within graphene networks for high-performance lithium storage. (1st September 2021) - Li, Yun; Yang, Wang; Liu, Xiaodong; Che, Sai; Tu, Zhiqiang; Hou, Liqiang; Xu, Chong; Liu, Hanlin; Huang, Guoyong; Zhou, Yasong; Li, Yongfeng
Highlights: An interfacial engineering strategy is developed. An epitaxial porous nanowire heterostructure is formed. The construction of NiO/NiCo2 O4 /CoO/Gra heterostructure with NiO/NiCo2 O4 and CoO/NiCo2 O4 interfaces. The double heterointerface structure enhances the electron conduction and Li + adsorption ability. Abstract: Rational construction of multidimensional composites with abundant heterointerfaces is still a persistent challenge, especially dual interface structure. Herein, a facile interface engineering strategy has been put forward to construct NiO/NiCo2 O4 /CoO heterostructures within graphene networks by controlling salt-templated solvothermal reactions and calcination treatments. The heterostructure produces dual interfaces of NiO/NiCo2 O4 and CoO/NiCo2 O4 . The resultant composite combines the merits of the unique properties of each component and exerts their synergistic effects. The density function theory calculations reveal that the interface structures can endow the hybrid with higher states at Fermi level, fast electron transfer, and efficient Li + adsorption ability. Furthermore, benefiting from the abundant active sites and porosity, this unique porous structure can accommodate the volume expansion and promote the diffusion of electrolyte ions, which greatly boosts the electrochemical performances of hybrids. Consequently, the NiO/NiCo2 O4 /CoO/Gra heterostructure electrodes achieve a remarkably reversible capacity of 1932.8 mAh g −1 at 0.1 A g −1, a superior rate capability (1210.5 mAh g −1 at 1 A g −1 ), and impressive cycling stability of 83.5% after 500 cycles at 0.5 A g −1 . This work provides a new insight of developing multiple heterostructures anode materials for high-performance energy storage and conversion. Graphical abstract: A facile interface engineering strategy is proposed to constuct a epitaxial porous heterostructure with dual interfaces of NiO/NiCo2 O4 and CoO/NiCo2 O4, which achieves high-performance and impressive cycle life for Li-ion batteries due to the rapid electrons transport and lithiation process of Li + . Image, graphical abstract